Automation of St. Francis Xavier's Seminary Library at Columbuthurai, Jaﬀna, Sri Lanka - Saverimuttu, A.G. (University of Jaffna, 2024)
The St. Francis Xavier's Seminary Library, a vital resource established forty years ago, specializes in Theology and Philosophy. Housing approximately 28,000 books, including encyclopaedias, subject dictionaries, multi-volume Bible commentaries, atlases, and various theological journals t plays a crucial role in theological education. Before automation, readers . I couldonlyrelyontheauthorcardcatalogueto ﬁndspeciﬁcbooks.Sinceothercardcatalogues wereincomplete,browsingtheshelveswasoftentheonlyeﬀectivemethodforlocatingbooks. Additionally, when a book was borrowed, the Library Assistant had to manually record the details on the Reader's Card and mark the return date on the book's slip. Recognizing the need to modernize and improve the library's eﬃciency, the Seminary Council initiated the automation project in June 2021 with a budget of Rs.1.5 million.The primary objectives were tostreamlinelibraryprocesses,enhanceservicedelivery,andmakeresourcesmoreaccessible tostudentsandstaﬀ.
Keywords: Library automation; Theology library; Library management; Digital transformation; Library services